A mutation-resistant deoxyribozyme OR gate for highly selective detection of viral nucleic acids. Issue 76 (13th September 2017) - Kamar, Ola; Sun, Sin-Cih; Lin, Chieh-Hua; Chung, Wan-Yu; Lee, Min-Shi; Liao, Yu-Chieh; Kolpashchikov, Dmitry M.; Chuang, Min-Chieh
Abstract : A set of deoxyribozyme probes was arranged in an OR gate to fluorescently report ∼90% of enterovirus 71 strains and distinguish them from coxsackievirus. Abstract : Highly selective probes hybridize only to fully complementary DNA or RNA sequences and, therefore, often fail to recognize mutated viral genomes. Here we designed a probe that possesses two seemingly incompatible properties: it tolerates some point mutations in genome, while it remains selective towards others. An OR deoxyribozyme logic gate was designed to fluorescently report the sequences of enterovirus 71 (EV71) covering ∼90% of all known EV71 strains. Importantly, sequences of closely related coxsackieviruses that differed by single nucleotides were reliably differentiated in 7 out of 8 cases.